Monitoring of Evapotranspiration Rate in Tabriz City Using SEBAL Algorithm with GIS and TRS Integration - Ali Sayyadi; Mohammad Javad Amiri; Mohamad Yazdi (علوم محیطی)
Introduction: The intricate choreography of evaporation and transpiration plays a fundamental role in the delicate ballet of the water cycle, serving as a linchpin for ecological equilibrium. Regrettably, more than 0.72% of a nation's water reservoirs slip through our fingers due to this natural process. The significance of precise predictions for evaporation and transpiration reverberates across a myriad of applications, encompassing agriculture, water resource management, irrigation planning, and the intricate modeling of plant growth. Robust studies on evapotranspiration, especially within the domains of climate change, sustainable development, and the management of water resources, underscore its indispensable importance. Nevertheless, the scarcity of meteorological stations and the resource-intensive nature of ground-based data collection have propelled an exploration into the realm of remote sensing techniques. Remote sensing techniques, when armed with accurate and fitting outputs, emerge as invaluable instruments for unraveling the intricacies of actual evaporation and transpiration.Among the plethora of algorithms residing within remote sensing, the Sabal algorithm stands out as a beacon of precision. Executing an instantaneous surface energy balance for each pixel in a satellite image, this algorithm becomes a powerful instrument for crafting accurate estimations. This investigation centers on the vibrant city of Tabriz, nestled in the western expanse of East Azerbaijan Province, Iran.Material and Methods: To unravel the enigmas of evaporation and transpiration in Tabriz, the Sabal algorithm and Landsat satellite images in sensors ("OLI_TIRS") spanning from 2013 to 2021 were enlisted. These images, procured from NASA, became the canvas for the meticulous strokes of remote sensing and geographic information systems (GIS). The harmonious fusion of thermal remote sensing techniques and GIS was orchestrated with precision, employing ARC GIS 10.8 and Envi 5.3 software for the intricate processes of data manipulation, analysis, and visualization.Results and Discussion: The findings of this research unveiled a visual metamorphosis since 2017, as the orange and red tones of Land Surface Temperature (LST) underwent a discernible escalation. Prevailing pixels exhibited temperatures spanning from 315 to 320 degrees and 320 degrees and above, marking a conspicuous warming trend in the surveyed area. The Normalized Difference Vegetation Index (NDVI) echoed this narrative, with yellow and red pixels (0.2-0.4) and (<0.6) illustrating an upward trajectory. The Brightness Temperature (BT) index joined the symphony of change, portraying an upward shift, as pixels in the 310-315 range yielded ground to 315-320 and 320 degrees and above. The tangible correlation between vegetation cover (NDVI) and land surface temperature resonated in the accurate depiction of the ascending trend in evaporation-transpiration from 2017 to 2021, particularly in the regions beyond the city center.Conclusion: In conclusion, this research illuminates the surge in evaporation-transpiration beyond Tabriz's city center, notably in regions experiencing a documented temperature increase. The documented correlation underscores the profound influence of climate variations on this indispensable process. It is recommended that, considering the research results indicating noticeable changes in evapotranspiration outside the city center in the years 2017, 2019, and 2021, future investigations utilize daily, monthly, and annual formulas. Factors such as land-use changes and meteorological variables like temperature statistics, precipitation, etc., should be thoroughly examined in upcoming research. And this topic is of utmost importance for sustainability.